Home Management of Childhood Diarrhoea by Mothers Presenting at a Tertiary Hospital in Bangladesh - Akhtaruzzaman, Muhammad; Hossain, Md Anwar; Choudhury, Ahmed Murtaza; Islam, Md Nazul; Dhar, Sonjib Kumar (Journal of Nepal Paediatric Society, 2016)
Introduction: Diarrhoea is a leading cause of under-five morbidity and mortality. Most of the diarrhoeal episodes are treated initially at home by mothers. The objective of the study was to assess mothers’ knowledge and practice of home management of diarrhoea. Material and Methods: This hospital based descriptive cross sectional study was carried out in Mymensingh Medical College Hospital. Three hundred and sixty children under five years of age having acute diarrhoea were included in the study by systematic random sampling. A structured pretested interview schedule was used to collect data. There were 11 knowledge and 11 practice questions; each was scored a point if correctly answered. The level of knowledge and the level of practice both were classified as poor for score 0-5 and good for score 6-11. Results: Of the 360 mothers, 45.55% had a good level of knowledge, while 33.89% had good level of practice. Both higher knowledge and practice score was significantly (p<0.001) associated with mother’s age, educational level and occupation and father’s educational level occupation and income. After adjusting for other factors, mother’s age was significantly associated with level of knowledge (p=0.003) and mother’s educational level was significantly associated with both level of knowledge (p=0.001) and practice (p=0.002) in home management of diarrhoea. Conclusion: The study has shown a low level of knowledge and practice in mothers regarding management of diarrhoea. The educational programs for mothers must be an essential part of the health facility programs. J Nepal Paediatr Soc 2015; 35(3): 237-246